PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS-ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 139 PEKANBARU - Rinova, Tesa; Marhadi, Hendri; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This observation was conducted by the IPS learning results which not achieve School KKM target score set by 70. The observations is conducted to Class IV SD Negeri 139 Pekanbaru Period 2017/2018. By applied Cooperative teaching methods Type Student Teams-Achievement Division (STAD) where first cycle conducted on March 5th until March 13th , 2018 and second cycle on March 20, until April 3th 2018. The observed student on Class IV SD Negeri 139 Pekanbaru are 23 students, the Observation was observe Teacher’s activities, student’s activities and learning result or students achievement. the observation shown the relations of teacher and students activities to learning result , teacher activities on first cycle first meeting is 42,5% within Minus category. Second meeting is 57,5% within enough category, by the second cycle first meeting is 65% within good category, and second meeting is 80% within good category. Look up to observed students learning result, will show the average score achieved by students is increased. On average basis score 60.00 with classical completion 30,43% (incomplete) . increased on first cycle Average score is 43,47 with classical completion 60.00% (incomplete) and second cycle 75,65 with classical completion 78,26%(complete). The observation conclude that applying Cooperative type learning method type Student Teams-Achievement Division (STAD) is able to increase learning achievement on Students Class IV SD Negeri 139 Pekanbaru.Keyword : STAD, social academic result